(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
Early latent fingerprint detection techniques included silver nitrate, ninhydrin, cyanoacrylate and iodine fuming which were less effective in developing fingerprints in robust condition as well as less stable for prolong period of time. With the upcoming advancements nanoparticles are now used for fingerprinting because of their great properties of surface area and optical properties. The quality of fingerprint development is found much better using nanoparticles. Therefore, this article summaries the broad application of different nanoparticles in the development and identification of latent fingerprints on various surfaces. Currently gold, silica and zinc oxide nano-particles have captivated the fingerprinting technology with their finest properties.